Stanmore noninvasive extendible endoprosthesis in the treatment of bone sarcoma in the preadolescent. Issue 2 (15th May 2019) - Sambri, Andrea; Staals, Eric; Medellin, Manuel Ricardo; Abudu, Adesegun; Gikas, Panagiotis; Pollock, Rob; Briggs, Tim WR; Donati, Davide Maria; Manfrini, Marco
Abstract: Aims: The aim of this study is to assess outcomes of patients ≤12 years who undergo Stanmore noninvasive extendible endoprosthetic replacement of the distal femur (DF NIEPR). Patients and Methods: A total of 101 children (mean age 9.6 years) were included. All complications which required further surgery were recorded. Clinical and functional outcomes were evaluated with Musculoskeletal Tumor Society (MSTS) scores at a mean follow‐up of 64 months (range 6‐174). Results: Thirty‐one (30.7%) patients died at a mean of 33 months. Forty had prosthesis removed after a mean of 43 months (range, 7‐103). Attaining of the full lengthening potential before skeletal maturity was the most frequent reason for revision surgery, particularly in those with smaller lengthening potential ( P   =  0.039). Implant survival rate for other causes was 61.7% at 5 years and 45.0% at 10 years. At final follow‐up mean MSTS score was 26 (range, 13‐29). Twenty‐two (21.5%) patients had a final limb‐length discrepancy (LLD)  > 2 cm. Conclusions: DF NIEPR produces a good functional outcome, with the prevention of major LLD at skeletal maturity in the majority of the cases. We suggest patient selection criteria to account for the stage of the disease due to the high cost of the NIEPR, and high percentage requiring revision, and a 60% mortality rate in those patients presenting with distant disease burden.